Necip El-Kilani hayatı-eserleri ve 20. yüzyıl arap edebiyatındaki yeri - Beyca, Fatma Betül (My University, 2008)
Bu çalıĢmada, XX. yüzyıl Arap edebiyatının öncülerinden birisi olan Necib el-Kîlânî ‟nin hayatı, eserleri, edebî kiĢiliğini iĢledik. AraĢtırmamız bir giriĢ ve üç bölümden oluĢmaktadır. GiriĢ bölümü iki kısımdır. Birinci kısımda Arap edebiyatı tarihiyle ilgili kısaca bilgi verilmiĢtir. Ġkinci kısmında ise Mısır ile ilgili genel bir bilgi sunulmaktadır. yazarın hayatıyla ilgilidir. Bu bölümde, yazarın hayatı Necib el-Kîlânî‟ye göre dönemin siyasi olayları, doğumu, ailesi ve çocukluğu, gençliği ve tahsili, edebî hayatı, siyasî hayatı, Ģahsiyeti ve ölümü baĢlıkları altında ele alınmıĢtır. Ġkinci bölüm, yazarın edebi yönünü içerir. Bu bölümde, el-Kîlânî‟nin üslubu, romanının özellikleri, edebi düĢünceleri, etkilendiği edebiyatçılar yer almaktadır. Üçüncü bölümde ise müellifin 20. yüzyıl Arap edebiyatındaki yeri ele alınmaktadır. IV

In this study, I have been carried out one of the leaders in the twentieth century Arabic literature Necib al-Kîlânî‟s life, works, literary character. My research consists of introduction chapter and three other chapters. The introduction chapter is divided into two sections. In the first section of the introduction chapter, there is brief information about history of the Arabic literature. The general information of Egypt, where the writer is from, is given in the second section of the same chapter. The first chapter is related with the writer‟s life. In this chapter writer‟s life mentioned with these subchapters; political events of the that period from the perspective of Necib el-Kîlanî, his birth, his family and childhood, his youth and education, his literary life, his character and his death. The second chapter is based on writer‟s literary aspects. In this chapter his style, properties of his novels, his literary aspects, authors whom el-Kîlanî affected from and his thoughts of Islamic literature and Islamic writers. The last chapter is about his place among 20th century Arabic literature. This chapter consists of author‟s position in the literature in 20th century Arabic world and his works.
Keywords: Arap Dili; Biyografi